2020
DOI: 10.1113/ep088192
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular reactivity to carbon dioxide is not influenced by variability in the ventilatory sensitivity to carbon dioxide

Abstract: Recent work demonstrated an influence of ventilation on cerebrovascular reactivity to CO 2 ; however, the concomitant influence of changes in mean arterial blood pressure (MAP) on ventilation-induced differences in cerebral blood flow (CBF) has yet to be examined in this context.Healthy participants (n = 15; 25 ± 3 years of age; 179 ± 6 cm height; 74 ± 10 kg weight; 3 female) underwent end-tidal forcing to increase their partial pressure of end-tidal CO 2 by +3, +6 and +9 mmHg above baseline in 5-min sequentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 45 publications
4
52
2
Order By: Relevance
“…Our results are consistent with several other studies that have reported that CVR is larger in the hypercapnic range compared to the hypocapnic range (Kety & Schmidt, 1948b;Ramsay et al 1993;Ito et al 2000;2003;Willie et al 2012;Coverdale et al 2014;Hoiland et al 2019). The relatively higher hypercapnic reactivity is probably partly a result of hypercapnia-induced elevations in blood flow to elicit an additive shear stress mediated vasodilatory response (Carter et al 2016;Hoiland et al 2017), such as increases in nitric oxide bioavailability (Mashour & Boock, 1999), as well as the CO 2 induced vasopressor response (Willie et al 2012;Regan et al 2014;Howe et al 2020;Webb et al 2020). A key new finding of this investigation is the paradoxical increase in hypocapnic CVR and reduction in hypercapnic CVR following NaHCO 3 infusion when expressed as CBF vs. [H + ] (rather than P aCO 2 ) ( Figs.…”
Section: Cerebrovascular Reactivity To [H + ]/Ph Is Regulated By Buffsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with several other studies that have reported that CVR is larger in the hypercapnic range compared to the hypocapnic range (Kety & Schmidt, 1948b;Ramsay et al 1993;Ito et al 2000;2003;Willie et al 2012;Coverdale et al 2014;Hoiland et al 2019). The relatively higher hypercapnic reactivity is probably partly a result of hypercapnia-induced elevations in blood flow to elicit an additive shear stress mediated vasodilatory response (Carter et al 2016;Hoiland et al 2017), such as increases in nitric oxide bioavailability (Mashour & Boock, 1999), as well as the CO 2 induced vasopressor response (Willie et al 2012;Regan et al 2014;Howe et al 2020;Webb et al 2020). A key new finding of this investigation is the paradoxical increase in hypocapnic CVR and reduction in hypercapnic CVR following NaHCO 3 infusion when expressed as CBF vs. [H + ] (rather than P aCO 2 ) ( Figs.…”
Section: Cerebrovascular Reactivity To [H + ]/Ph Is Regulated By Buffsupporting
confidence: 92%
“…Notably, this method of arterial blood gas alteration provides a lesser end‐tidal‐to‐arterial PnormalCO2 gradient, precludes any independent influence of V̇E on cerebrovascular CO 2 reactivity (Howe et al . 2020) and therefore provides an accurate stimulus–response relationship (Fisher, 2016; Fisher et al . 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CO 2 inhalation from a reservoir/Douglas bag), precludes any influence of V̇ E on CVR (Howe et al . 2020), and therefore provides an accurate quantification of stimulus response relationships (Fisher, 2016; Fisher et al . 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, this method of arterial blood gas manipulation provides lesser arterial-to-end-tidal gradients of P ET CO 2 than other methods of blood gas manipulation (e.g. CO 2 inhalation from a reservoir/Douglas bag), precludes any influence of VĖ on CVR (Howe et al 2020), and therefore provides an accurate quantification of stimulus response relationships (Fisher, 2016;Fisher et al 2018). This gas delivery system was used for both the cFMD and CVR tests described below.…”
Section: Experimental Measuresmentioning
confidence: 99%